PENGEMBANGAN BUDAYA DAN TOLERANSI DALAM MEMBANGUN KEBERAGAMAN MASYARAKAT DI MA’HAD AL-ZAYTUN - Ngainnur Rohmah, Siti; Nur Afifah, Muthia; Alimatul Zahro, Nur; Partono; Wawan (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
In the era of globalization, the diversity of society is becoming increasingly complex, presenting a significant challenge in building social harmony and stability. Culture and tolerance play a crucial role in managing this diversity. Ma'had Al-Zaytun, as an Islamic educational institution in Indonesia, holds a strategic role in shaping culture and tolerance within the community at Ma'had Al-Zaytun. The aim of this research is to gain a deeper understanding of the strategies and approaches employed by Ma'had Al-Zaytun in fostering culture and tolerance in promoting diversity within the community at Ma'had Al-Zaytun. This research employs a literature review method to collect data from various relevant sources regarding the development of culture and tolerance in fostering community diversity at Ma'had Al-Zaytun. The results show that Ma'had Al-Zaytun has successfully developed culture and tolerance through intercultural training programs, interfaith discussions, and the teaching of tolerance values, which have enhanced understanding and tolerance attitudes among all members of the academic community. Tolerance education is applied in daily life through student exchange programs and religious celebration events. Close collaboration and regular evaluation are necessary to strengthen these programs and ensure that tolerance values remain integrated. This success serves as a model for other educational institutions in building a harmonious and open society in line with the spirit of Indonesia's diversity. Keywords: Development, Culture, Tolerance, Ma'had Al-Zaytun